An evidence-based review of CGRP mechanisms in the propagation of chronic visceral pain. Issue 3 (September 2020) - Urits, Ivan; Li, Nathan; Bahrun, Ehab; Hakobyan, Hayk; Anantuni, Lekha; An, Daniel; Berger, Amon A.; Kaye, Alan D.; Paladini, Antonella; Varrassi, Giustino; Vorenkamp, Kevin E.; Viswanath, Omar
Abstract : Chronic pain is typically defined as pain that persists after acute tissue damage and inflammation or as pain that follows a chronic disease process and lasts more than three months. Because of its debilitating impact on the quality of life of patients, recent research aims to investigate the mechanisms behind nociception to discover novel therapeutic agents to alleviate pain. One such target is the neuropeptide calcitonin gene-related peptide (CGRP), which has shown to play an integral role in migraine pathophysiology. Effective treatments of migraines with CGRP antagonists have stimulated our efforts toward checking a possible involvement of CGRP in nonheadache pain conditions such as hypertension, congestive heart failure, Alzheimer's disease, and vascular ischemia. Here, we provide a brief overview of chronic pain, with a particular emphasis on the role of CGRP as a fundamental mediator of nociceptive pain as well as a target for novel therapeutic agents.